Is Kiai a Transformational Leadership Model? - Putro, Setyanto; Risdiana, Aris; Jihan Fitri, Fatimatus Zahro’; Harminingsih, Harminingsih (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2022)
This study examines the social conflicts faced by mosque and prayers room managers in the Cangkringan area of Sleman Regency, Yogyakarta Province. The social conflicts encompass a wide range of issues, from waqf land disputes to inheritance distribution and domestic household problems such as divorce to theological differences related to superstition, bid’a, and superstition. In Kapanewon (districts) Cangkringan, fewer than one hundred mosques and prayer rooms deal with such issues. To accomplish the study, this research was conducted using a qualitative design. A sociological approach was utilized to examine the roles and functions of Kiai and Islamic Boarding Schools in Kapanewon Cangkringan in general and mosque and prayer room managers in particular. The theory used is Max Weber's leadership theory. Three essential aspects of internal processes were identified in this study. First and foremost, the leadership of Kiai, the leader of the al-Qodir Islamic boarding school, exemplified a participatory transformative leadership who is not afraid of taking different perspectives to achieve common goals. Secondly, the transformative leadership at Islamic boarding school Kiai take a primary role as facilitator and problem solver for a wide range of social conflicts. As a third aspect, conflict resolution was distributed by establishing a new system with mutually agreed regulations, and it took place with the Selapanan system every Kliwon Sunday. In addition to enriching interdisciplinary intellectual treasures, this research contributes to interdisciplinary treasures both in sociology, particularly transformative leadership, and management science, specifically in organizational leadership.